New Developed Analytical-Chemiluminometric (Sensitized) Continuous Flow Injection Analysis, for Determination of Ciprofloxacin; Application to Pharmaceutical Preparation - Al-Hashimi, Issam M A Shakir; Al-Awadi, Nagam Shakir Turkie (Al-Nahrain Journal of Science, 2018)
A newly developed analytical method characterised by its speed and sensitivity for the determination of ciprofloxacin via the improvement of the chemiluminescence system for luminol-H2O2-OH--ciprofloxacin via continuous flow injection analysis. The method is based on the indirect chemiluminescence-reaction (Sensitized) via the improvement of the amount of photons released through the oxidation of luminol-H2O2-OH- in the presence of ciprofloxacin as a sensitizer for the reaction. Linear dynamic range for the chemiluminescence-emission vs. ciprofloxacin concentration was 0.01-1 mmol.L-1 while C.O.D was 96.64%. The L.O.Q was 203 ng/sample. L.O.D. (S/N=3) = 6.01ng/sample from the stepwise dilution for the minimum concentration of lowest concentration in the linear dynamic ranged of the calibration graph. R.S.D.% for n=10 was